Melodic bridges: music intervention as a catalyst for social skills development in preschool children with autism - Yang, Jinjin; Zhang, Runyi (Frontiers in Psychology, 2025)
Autism spectrum disorder (ASD) is characterized by persistent challenges in social communication, emotional regulation, and cooperative behavior. While traditional behavioral therapies are widely used, they can lack engagement and flexibility. Music interventions, by engaging multiple neural and emotional systems, offer a promising alternative to address these core deficits. This randomized controlled trial (RCT) evaluated the efficacy of a 12-week structured music intervention in improving social skills in preschool children with ASD. Sixty participants (aged 3–6 years) were randomly assigned to an experimental group (music intervention) or a control group (behavioral therapy). Therapeutic music activities included rhythm training, interactive singing, instrumental improvisation, and group games, conducted three times weekly. Social skills were assessed using the Social Responsiveness Scale (SRS) and observational data at baseline (T0), mid-intervention (T1), post-intervention (T2), and six-week follow-up (T3). The music intervention demonstrated significant improvements in social communication, emotional regulation, and social motivation compared to the control group. Interactive singing showed the strongest impact on social communication, fostering verbal reciprocity and turn-taking. Rhythm training enhanced social motivation and joint attention, while instrumental improvisation improved emotional regulation by providing a non-verbal outlet for self-expression. Group games facilitated peer interaction and cooperation. These improvements were sustained at T3, underscoring the intervention’s durability. This study highlights the transformative potential of music interventions in addressing core social deficits in preschool children with ASD. By leveraging rhythm, melody, and improvisation, music therapy offers a scalable, engaging, and effective therapeutic approach. These findings support the integration of music-based interventions into early education and clinical settings, paving the way for more personalized and inclusive therapies for ASD.